Optimization of dialdehyde soluble soybean polysaccharide: preparation by response surface methodology for cleaner leather tanning. Issue 12 (7th March 2022) - Zhu, Haolin; Liu, Hui; Tang, Keyong; Liu, Jie; Zheng, Xuejing; Pei, Ying; Zhong, Jide
Abstract : Leather is widely used in daily necessities, such as shoes and bags. Abstract : Leather is widely used in daily necessities, such as shoes and bags. Traditional chrome tanning might produce leathers with excellent mechanical and thermal properties but gives rise to problems, such as environmental pollution. To find an ecological alternative for chrome-tanning agents, soluble soybean polysaccharide (SSPS) was oxidized by sodium periodate to yield dialdehyde soluble soybean polysaccharide (DPA). By the response surface methodology (RSM)-based optimization of the preparation process, DPA was obtained at the optimized condition at the mass ratio of 1 : 1.9, oxidation time of 0.53 h, and oxidation temperature of 20 °C, and the hydrothermal shrinkage temperature of the DPA-tanned leather reached 79 °C. The Fourier transform infrared (FT-IR) spectra and gel permeation chromatography (GPC) showed that the aldehyde group was successfully introduced, and the molecular weight was significantly reduced. The DPA-tanned leather has good collagen fiber dispersion and mechanical properties and thus is suggested to be a green tanning agent for leather making.